PENDEKATAN KEPEMIMPINAN LINTAS BUDAYA DAN ANTAR NEGARA DI ASIA DAN BARAT - REGY CITRA PERDANA; ANA YULIANA; DEDI HARTAWAN (Niagawan, 2020)
Abstract  This study aims to determine cross-cultural leadership between countries in Asia and in western countries, this is because leaders have subordinates consisting of different cultures, ethnicities, social status, and citizenship. Culture, values, norms, and ethics have an influence on the attitude of a leader in behavior. Although there are many differences in culture, attitudes, and language used in behaving as a leader, many studies have shown similarities in leadership between western countries and countries in Asia. These similarities are shown in the same perception about leadership. The many differences are influenced by culture, so in cross-cultural leadership needed leaders who have competence. Keywords: Leadership, Across Culture, Asian and Western Countries